2022
DOI: 10.1002/ijgo.14269
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in updating national guidelines and essential medicines lists in Sub‐Saharan African countries to include WHO‐recommended postpartum hemorrhage medicines

Abstract: Despite the 2017 WHO recommendations on tranexamic acid (TXA) for the treatment of postpartum hemorrhage (PPH), the 2018 uterotonic recommendations (which included heat‐stable carbetocin (HSC) for the prevention of PPH) and their inclusion in the WHO Essential Medicines List (EML), both drugs are still underused or not used at all to manage PPH in many countries with a high burden. HSC is currently being registered in low‐ and middle‐income countries and its policy inclusion is limited and slow. TXA (also heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Policy translation from national to subnational level can be challenging as evidenced in our assessment where most respondents, regardless of role, were either unable to articulate subnational level policies or indicated that they did not exist. This challenge has been documented elsewhere in Sub-Saharan Africa where new guidelines for postpartum hemorrhage management were not disseminated effectively to frontline workers [33]. This may be related to the influence of social networks maintained by providers and DHMT staff.…”
Section: Discussionmentioning
confidence: 99%
“…Policy translation from national to subnational level can be challenging as evidenced in our assessment where most respondents, regardless of role, were either unable to articulate subnational level policies or indicated that they did not exist. This challenge has been documented elsewhere in Sub-Saharan Africa where new guidelines for postpartum hemorrhage management were not disseminated effectively to frontline workers [33]. This may be related to the influence of social networks maintained by providers and DHMT staff.…”
Section: Discussionmentioning
confidence: 99%